2020
DOI: 10.2196/15057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Electronic Health Management Program for Patients With Cardiovascular Risk: Randomized Controlled Trial

Abstract: Background In addition to medication, health behavior management is crucial in patients with multiple risks of cardiovascular mortality. Objective This study aimed to examine the efficacy of a 3-month Smart Management Strategy for Health–based electronic program (Smart Healthing). Methods A 2-arm randomized controlled trial was conducted to assess the efficacy of Smart Healthing in 106 patients with at least… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…In recent years, new network information technology has been mainly developed on artificial intelligence, databases, and fifth-generation (5G) networks, and the rudiment of a complex and comprehensive digital society has been gradually shown. Therefore, the development of electronic health management becomes an inevitable phenomenon [ 1 3 ]. A latest survey report released by the Global Web Index (GWI) shows that social media users account for 98% of global Internet users.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, new network information technology has been mainly developed on artificial intelligence, databases, and fifth-generation (5G) networks, and the rudiment of a complex and comprehensive digital society has been gradually shown. Therefore, the development of electronic health management becomes an inevitable phenomenon [ 1 3 ]. A latest survey report released by the Global Web Index (GWI) shows that social media users account for 98% of global Internet users.…”
Section: Introductionmentioning
confidence: 99%
“…The 12-week ICT program, Smart Management Strategy for Health (SMASH), includes an application and a web-based program. 9 This ICT program consisted of four areas: self-assessment, self-planning, selflearning, and self-monitoring by automatic feedback. Program targets included positive thinking, a balanced diet, physical activity, and medication adherence.…”
Section: Study Design and Randomizationmentioning
confidence: 99%
“…5,6 A number of interventions have been tested using mobile health (mHealth) or telehealth interventions. 7,8 Health coaching has been shown to improve patient self-management 9 and is cost-effective. 10,11 Health coaching can improve use of ICT programs.…”
Section: Introductionmentioning
confidence: 99%
“…7 , 8 Disease management programs for hypertensive and diabetic patients have been shown to primarily promote adherence to medication. 9 , 10 Numerous studies have recently been published on mobile health (mHealth)-based disease management programs for hypertension 11 13 and diabetes. 11 , 13 17 These studies generally reported positive effects, such as improved blood pressure control 13 and blood glucose control, 13 – 16 as well as lifelog data, such as body weight and the number of steps.…”
mentioning
confidence: 99%
“… 9 , 10 Numerous studies have recently been published on mobile health (mHealth)-based disease management programs for hypertension 11 13 and diabetes. 11 , 13 17 These studies generally reported positive effects, such as improved blood pressure control 13 and blood glucose control, 13 – 16 as well as lifelog data, such as body weight and the number of steps. mHealth-based disease management programs also collect application-related information, such as device usage 11 and user engagement, 16 which predicts the effectiveness of improvements in outcomes.…”
mentioning
confidence: 99%